Genetic Analysis and Mapping of an Enclosed Panicle Mutant Locus esp1 in Rice (Oryza sativa L.) - Yuan-lin DUAN; Hua-zhong GUAN; Ming ZHUO; Zhi-wei CHEN; Wen-tao LI; Run-sen PAN; Da-mei MAO; Yuan-chang ZHOU; Wei-ren WU (Journal of Integrative Agriculture, 2012)
A mutant was isolated from the M2 of 60Co-γ ray mutagenized male-fertility restorer line Zao-R974 in rice. The mutant showed pleiotropic phenotypes including dwarfism, delayed heading time, short and partially enclosed panicles, short uppermost internode, decreased grain and secondary branch numbers per panicle, and partially degenerated spikelets. The mutant was named as esp1 (enclosed shorter panicle 1). Genetic analysis indicated that the mutant phenotype was controlled by a recessive locus. Spraying exogenous GA3 did not rescue the panicle enclosure. Using an F2 and a BC1 population of the cross between esp1 and a japonica cultivar Nipponbare, we mapped the ESP1 locus to a region of ∼260 kb on chromosome 11. This result provides a basis for further map-based cloning of the ESP1 locus.